Effect of Antimicrobial Peptides on the Growth and Immunity of Swamp Eels - Shyh-Shyan Jan; Dai-Qing Yang; Rommanee Thammasena (Department of Aquaculture, 2021)
This study aimed to investigate the effect of different levels of antimicrobial peptides (AMPs) supplementation in the diet feed on growth performance, survival rate, biochemical parameters in swamp eels. Healthy fishes were randomly assigned to five groups feeding with different supplementation of AMPs (0, 200, 400, 600, or 800 mg/kg) in diets for 68 days. Results showed that relative weight gain, feed coefficient and survival rate were significantly (p<0.05) increased by supplementation of AMPs in feed. Level of protein (TP), triglyceride TG, alanine transaminase (ALT), alkaline phosphate (ALP), acid phosphate (ACP), superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT) in the serum were significantly (p<0.05) improved in all AMPs treatments, while no significant difference was found between the control and AMPs 200 mg/kg. AMPs supplementation significantly enhanced (p<0.05) the survival rate and immune protection in swamp eels after challenged with Aeromonas hydrophila compared to the control group and eels fed with AMPs 800 mg/kg had the highest survival rate and immune protection (32.50 and 85.71%, respectively). The diets containing AMPs enhanced the survival rate, immune ability, and antioxidant capacity in swamp eels, indicate that an appropriate dosage of AMPs can be used as a potential alternative to antibiotics in swamp eels.